The enlightenment against the Baroque : economics and aesthetics in the eighteenth century - Saisselin, Rémy G. (Rémy Gilbert), 1925- (Berkeley : University of California Press, 1992)
How do the seemingly disparate arenas of Enlightenment philosophy, economic theories, boudoir etiquette, literary styles, and artistic modes coincide in the late eighteenth century? In his poetic essay on the evolution of the idea of luxury and art, Remy Saisselin plots their intersection through precise, witty examples. Saisselin convincingly describes the development of our modern taste, ultimately the successor of the more spiritual and grand baroque taste. His analysis both illuminates and distinguishes between eighteenth-century and modern varieties of conspicuous consumption.
In this elegant and persuasive Pascalian disquisition, Saisselin depicts the rise of luxe as an escape from ennui, especially for its major proponents like Madame de Pompadour. Further, the author shows that in the eighteenth century, for the first time in European history, a significantly large class of wealthy, leisured people emerged to make art, luxury, and the avoidance of boredom more widespread preoccupations than previously thought. By drawing on a wide variety of contexts, Saisselin provides a lucid picture of the first phases in the emergence of a specifically bourgeois taste arising from the contradictions between luxury and economic theory.
Pascal's room, Mandeville's bees, and Baroque spending: art or luxury? luxury as disease -- "Doing in" the baroque: were the court and the Parisian social elite of the eighteenth century a consumer society? -- Redesigning the ancien regime -- The earthly city of the eighteenth-century philosophies -- True taste recovered and the Baroque transfigured -- Changing appearances: from court to beau monde -- Conclusion: the end of the Baroque and the invention of aesthetic art.
Includes bibliographical references (pages 143-148) and index.
Print version record.
English.
JSTOR
Keywords: Europe -- Civilization -- 18th century; Civilization, Baroque; Enlightenment; Europe -- Civilisation -- 18e siècle.; Civilisation baroque; Siècle des Lumières.; Enlightenment (18th-century western movement); HISTORY -- Europe -- Western; Civilization; Civilization, Baroque; Enlightenment; Europe; 15.70 history of Europe; Verlichting (cultuurgeschiedenis); Barok; Economische filosofie; Kunst; Weelde; Civilization, Baroque; Europe, Western -- Civilization -- 18th century; 1700-1799